ACADEMIC WORDS IN BUKU BAHASA INGGRIS KELAS XII - Ely Heldydiana Selamat (Jurnal Pendidikan dan Kebudayaan Missio, 2018)
Academic Words in Buku Bahasa Inggris Kelas XII. In learning English as a foreign language (EFL), students have to learn vocabulary and its meaning as vocabulary helps them to understand what they hear, to speak in communication, to understand written text and to construct good sentences in writing. In academic field, the words that should be known by the students are academic words. The academic words widely used in academic textbooks and journals named academic word list. Vocabulary Profiler used in this study was a web profiler program developed by Tom Cobb. The profiler is an online program available at www.lextutor.ca/vp. This program helped the researcher to analyze the AWL in a course Buku book Bahasa Inggris kelas XII. The tool counted a total number of words and also the percentage of words appeared: 1000 most frequent words, 2000 most frequent words, academic words, and off list words. The data of the Web Vocabulary Profilers English version 3 described the percentage of AWL in the Buku Bahasa Inggris Kelas XII. For secondary students, course book might be one of the tools to get inputs in term of vocabulary. Asa key component in language class text books have a significant role on language classes. Considering the important role of course book and the necessity of academic vocabulary in a course book, the present study aimed to analyze Academic Words in Buku Bahasa Inggris Kelas XII.